Annoyance Evaluation of Subway Interior Noise Based on Psychoacoustical Indices. (October 2013) - Liu, N.N.; Wang, Y.S.; Shi, L.
The subjective and objective method of sound quality evaluation (SQE) in respect of subway interior noise is discussed in this paper. A sample subway of Shanghai Metro Line 9 is considered. The noise signals at four locations and two sets of dummy head heights are measured under three common working conditions of the subway. The measured noises are subjectively evaluated for annoyance values by using the grouped pair-comparison method. Several objective psychoacoustical parameters of these samples are calculated. Accordingly, a mathematical model of sound annoyance is established by using the correlation analysis and multi-dimensional linear regression method, in which the loudness, sharpness, etc., are taken as the variables. The experimental verifications show that there has a strong correlation between the model predicted and subjectively evaluated results, which suggest a good prediction accuracy of the newly presented model.